TRENDS IN THE DEVELOPMENT OF MODERN EDUCATION AND PEDAGOGY - Alieva Н; Tleumuratova М (MMIT Proceedings, 2023)
Modern education and pedagogy are among the most important areas in the modern world. They reflect the current state of society and determine its future. The task of science and practice in this direction is to find new approaches and teaching methods that would meet the needs of not only society, but also each individual. Every year the requirements for education and teaching methods change, which requires constant development of pedagogical technologies and techniques. In this article we will consider the main trends, problems and prospects for the development of modern education and pedagogy